2014
DOI: 10.1371/journal.pone.0105900
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Practices, and Perceived Barriers Regarding Cancer Pain Management Among Physicians and Nurses In Korea: A Nationwide Multicenter Survey

Abstract: PurposeMedical professionals’ practices and knowledge regarding cancer pain management have often been cited as inadequate. This study aimed to evaluate knowledge, practices and perceived barriers regarding cancer pain management among physicians and nurses in Korea.MethodsA nationwide questionnaire survey was administered to physicians and nurses involved in the care of cancer patients. Questionnaire items covered pain assessment and documentation practices, knowledge regarding cancer pain management, the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
67
5
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 25 publications
15
67
5
2
Order By: Relevance
“…This variation was also noticed by other conducted studies [21, 23, 35, 41, 50] and could be due to inadequate educational curriculum and insufficient clinical training programs [23, 26, 44, 51]. …”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This variation was also noticed by other conducted studies [21, 23, 35, 41, 50] and could be due to inadequate educational curriculum and insufficient clinical training programs [23, 26, 44, 51]. …”
Section: Discussionsupporting
confidence: 59%
“…Mostly what they show was that in general many HCPs, especially nurses, lack adequate knowledge about pain, which led to undertreatment of pain [13, 1823]. Studies had also shown that HCPs bear misconceptions and myths about pain that impede proper pain management [22, 2427].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that improving pain assessment procedures requires the caregiver to acknowledge and have faith in the patient's report (Jho et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Medical professionals' practices and knowledge regarding cancer pain management have been said as inadequate, especially due to differences between physicians and nurses in knowledge and practices for cancer pain management [46]. Effective communication is needed for optimal cancer pain management [47].…”
Section: General Approach In Cancer Pain Managementmentioning
confidence: 99%